New developments for lignocellulosics-nanocomposites with low carbon footprint - Leao, Alcides L. [UNESP]; Cherian, Bibin M. [UNESP]; Souza, Sivoney F.; Sain, Mohini; Narine, Suresh (Springer Nature, 2012)
Cellulose nanofibrils have been evaluated as reinforcement material in polymeric matrixes due to their potential to improve the mechanical, optical, and dielectric properties of these matrixes as well as its environmental positive footprint. This work describes how banana nanocellulose can be used to replace others not so friendly materials in many applications including, biomaterials, automotive industries and packaging by proved with their mechanical properties. The process used is very mild to the environment and consists of a high pressure fibrillation followed by a chemical purification which affects the fiber morphology. Many fibers characterization processes were used including microscopy techniques and X-ray diffraction to study the structure and properties of the prepared nanofibers and composites. Microscopy studies showed that the used individualization processes lead to a unique morphology of interconnected web-like structure of the fibers. © 2012 Materials Research Society.
Keywords: Cellulose nanofibrils; Chemical purification; Fiber morphology; Microscopy technique; Polymeric matrix; Reinforcement materials; Structure and properties; Unique morphologies; Automotive industry; Biological materials; Biomaterials; Carbon footprint; Dielectric properties; Mechanical properties; Morphology; X ray diffraction; Packaging materials; Anatomy; Carbon; Dielectric Properties; Mechanical Properties; Packaging Materials; X Ray Diffraction